Factors Influencing the Adoption of Passenger Electric Vehicles: A Focus on Eastern India (Journal of Informatics Education and Research, 2025)
The adoption of passenger electric vehicles (EVs) in India is gaining traction, driven by environmental concerns, government policies, and advancements in EV technology. However, the rate of adoption varies across regions, with Eastern India facing unique challenges and opportunities. This study examines the key factors influencing EV adoption in this region, including economic considerations, infrastructure development, consumer awareness, and policy incentives. Limited charging infrastructure, high initial costs, and a lack of widespread awareness hinder widespread adoption, while rising fuel prices, government subsidies, and increasing environmental consciousness act as major drivers. The study also highlights the role of state-level policies and private sector investments in shaping the EV landscape in Eastern India. Understanding these factors is crucial for stakeholders, including policymakers, manufacturers, and consumers, to facilitate a smoother transition toward sustainable mobility. By addressing infrastructural gaps and financial barriers, the EV market in Eastern India can witness significant growth. The findings of this study contribute to the broader discourse on sustainable transportation and provide valuable insights for improving EV adoption strategies in the region.